Design and simulation of proposed automation system in existing manufacturing work environment - Salam, Zainila (2013)
The manual operation may impact fluctuation in daily productivity. Manual processing also lead to increase in the number of queues, poor management of Work in Process (WIP) resulting in that impact low productivity. The objective of this project is to propose an automation system that would improve productivity on actual manufacturing assembly area and validate the proposed system with maximize headcount utilization. This project develop modelling of the production system was performed using through ARENA simulation software that evaluates the impact of manufacturing productivity before and after the implementation of the proposed automation system improvement. The system simulation development will be based on assembly processt at PHN Industry, USJ. The main results showed that productivity has improved by 39% due to changes in implementation of conveyor system as part of the automation development based on simulation study. This validates the changes to the work process flow through a simple conveyor system to replace MHS. Further improvement on the simulation process in areas such as queue analysis on the time and number of parts waiting time could add greater complexity to the model resulting in increased of productivity.